The influence of potential outcomes of corporate social responsibility engagement factors on SME competitiveness - E. Venter; P. Turyakira; E. E. Smith (South African Journal of Business Management, 2014)
While SMEs are globally recognised for their importance in the social and economic development of many economies, their survival and competitiveness has remained a cause for concern. More than half of SMEs in Uganda fail during their first year. Analytical and empirical research on appropriate strategies for SMEs' competitiveness in Uganda is limited. The potential outcomes of CSR engagement such as employee satisfaction, business reputation, and customer loyalty have been found to be positively related to the competitiveness of SMEs. The primary objective of this article is to identify and empirically test the factors that influence the competitiveness of SMEs in Uganda. A structured selfadministered questionnaire was distributed to 750 potential SME respondents. The respondents were identified using purposive sampling technique, and the data were collected from 3 83 usable questionnaires. An exploratory factor analysis was conducted, and Cronbach-alpha coefficients calculated to determine the discriminant validity and reliability of the measuring instrument. Correlations were analysed using Structural Equation Modeling. The empirical results of this study indicate that Employee satisfaction, Business reputation, Customer loyalty and Stakeholder trust significantly impact the competitiveness of SMEs.
Keywords: 650